Getting it Right: What to Reform in International Financial Markets - Ricardo Hausmann; Eduardo Fernández-Arias (Inter-American Development Bank, Research Department, 2000)
Our review of the main proposals on international financial architecture currently under consideration gives reasons for concern that excessive emphasis on improving stability by impeding capital flows will have a deleterious development impact. Sustainable development requires initiatives addressing the failures of international financial markets that make capital flows so small and volatile. Our analysis identifies a number of alternative initiatives and principles to get them right in connection with official support, private sector participation, and reforms to the institutional framework. However, the fact that some of these efficient reforms entail financial risks to supporting developed countries contributes to lack of consensus.
Keywords: 330; Internationaler Finanzmarkt; International; Privatwirtschaft; Welt; Lender of Last Resort